2018
DOI: 10.1093/cid/ciy634
|View full text |Cite
|
Sign up to set email alerts
|

Immune Priming and Long-term Persistence of Memory B Cells After Inactivated Poliovirus Vaccine in Macaque Models: Support for at least 2 Doses

Abstract: BackgroundAs a risk-mitigation strategy to minimize paralytic polio following withdrawal of Sabin type 2 from the oral poliovirus vaccine in April 2016, a single full dose or 2 fractional doses of inactivated poliovirus vaccine (IPV) are recommended. However, limited knowledge exists on long-term persistence of immune memory following 1- or 2-dose IPV schedules.MethodsWe examined induction and maintenance of immune memory following single- vs 2-dose IPV schedules, either full-dose intramuscular or fractional-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…For example, Bhaumik et al investigated the long-term persistence of immune memory following oneor two-dose inactivated poliovirus vaccine schedules. They showed that memory B cells can be induced by both vaccine regimens, although this cell subset declined by five months after a single immunization, whereas it persisted for more than one year with the twodose strategy [59]. Additionally, identifying predictive biomarkers at baseline, i.e., before vaccination, has drawn interest from researchers who reported proof-of-concept results on influenza [60,61], yellow fever [62], and hepatitis B [63] vaccines.…”
Section: At What Time Should We Identify Vaccine Response Biomarkers?mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bhaumik et al investigated the long-term persistence of immune memory following oneor two-dose inactivated poliovirus vaccine schedules. They showed that memory B cells can be induced by both vaccine regimens, although this cell subset declined by five months after a single immunization, whereas it persisted for more than one year with the twodose strategy [59]. Additionally, identifying predictive biomarkers at baseline, i.e., before vaccination, has drawn interest from researchers who reported proof-of-concept results on influenza [60,61], yellow fever [62], and hepatitis B [63] vaccines.…”
Section: At What Time Should We Identify Vaccine Response Biomarkers?mentioning
confidence: 99%
“…Additionally, preclinical models are often instrumental in appraising long-term immune memory, as longitudinal studies can be initiated and conducted more easily and rapidly than in human populations. For example, NHPs have been successfully used to study memory responses induced by vaccines against SIV, tuberculosis, and or polio [59,[217][218][219]. Implementing systems vaccinology techniques in prolonged longitudinal preclinical studies [72] could link initial and long-term responses and generate early signatures of immune memory.…”
Section: Defining New Correlates Of Protectionmentioning
confidence: 99%
“… 1 2 3 4 5 6 7 8 9 10 11 12 Such cross-reactivity is not evident in experimental infections of primates. 13 Actually, following preclinical studies performed in primates 14 15 16 17 18 as recommended by the Food and Drug Administration, 19 the reports declare that primate active immunization by pathogen vaccine administration is well tolerated and exempt of relevant events. Hence, the questions: why the potential cross-reactivity and the consequent potential autoimmune sequelae do not occur in primates following experimental infections or during preclinical tests?…”
Section: Introductionmentioning
confidence: 99%
“…IPV and OPV are both effective in preventing polio disease. However, the use of OPV can cause rare cases of vaccine-associated paralytic poliomyelitis, as well as a significant resurgence of poliomyelitis cases due to circulating vaccine-derived poliovirus [ 8 , 9 ] and low vaccination coverage in some countries [ 10 , 11 ]. For this reason, the core of the Polio Eradication and Endgame Strategic Plan implemented by the Global Polio Eradication Initiative is to introduce IPV into routine immunization programs worldwide, as a replacement for OPV [ 2 , 12 , 13 ].…”
mentioning
confidence: 99%